2012
DOI: 10.1016/j.ydbio.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane cholesterol depletion disrupts prechordal plate and affects early forebrain patterning

Abstract: Cholesterol-rich membrane microdomains (CRMMs) are specialized structures that have recently gained much attention in cell biology because of their involvement in cell signaling and trafficking. However, few investigations, particularly those addressing embryonic development, have succeeded in manipulating and observing CRMMs in living cells. In this study, we performed a detailed characterization of the CRMMs lipid composition during early frog development. Our data showed that disruption of CRMMs through met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Possibly a reduced membrane biosynthesis or reduced lipid storage due to inhibition of the glucosylceramide biosynthetic pathway by miglustat is responsible for the reduced brain weights of combination- and miglustat-treated mice [42]. For methyl-β-cyclodextrin (MβCD) it has recently been shown that plasma membrane cholesterol depletion affects early forebrain patterning in Xenopus [43]. MβCD-injected embryos displayed reduced eyes or lack eyes entirely, most likely because of loss of neural tissue from where these structures derive.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly a reduced membrane biosynthesis or reduced lipid storage due to inhibition of the glucosylceramide biosynthetic pathway by miglustat is responsible for the reduced brain weights of combination- and miglustat-treated mice [42]. For methyl-β-cyclodextrin (MβCD) it has recently been shown that plasma membrane cholesterol depletion affects early forebrain patterning in Xenopus [43]. MβCD-injected embryos displayed reduced eyes or lack eyes entirely, most likely because of loss of neural tissue from where these structures derive.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that lipid rafts are present during early Xenopus development (Reis et al, 2012). However, little is known about their occurrence and function during kidney development.…”
Section: Resultsmentioning
confidence: 99%
“…Mevinolin) disrupts signaling events mediated by lipid rafts (Klein et al, 1995; Taraboulos et al, 1995). They cause dramatic defects during embryonic development affecting signaling pathways like sonic hedgehog and Wnt (Cooper et al, 2003; Tadjuidje and Hollemann, 2006; Anderson et al, 2011; Reis et al, 2012). Similarly, mice lacking protein components of lipid rafts such as Caveolin-1 display a wide range of embryological defects (Drab et al, 2001; Razani et al, 2001; Zhao et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Which was illustrated by Sox2 diminished expression only at the anterior neural plate region (Fig. 3c), as well as the mispatterned expression of Otx2 and Six3 (Reis et al, 2012). Then, we went further on and specified, through transplantation experiments, the developmental window in which the head mesoderm/prechordal plate gets compromised.…”
Section: Prechordal Plate and Anterior Neural Plate Let's Form The Headmentioning
confidence: 99%